Ba'á¸u Al-NamÄdzij Fi IstikhdÄm Al-KalimÄt Al-MutaqÄá¹i'ah Ligharaá¸ Istiáº“hÄri Al-MufrodÄt - budi, Firmansah Setia Budi; Rohanda Rohanda (Program Studi Pendidikan bahasa Arab IAIN Langsa, 2024)
The vocabulary is considered the learner's capital for the target language in terms of speaking, communicating, or conversing in it. The problem that learners often face in this regard is the difficulty of retrieving the vocabulary they need when speaking. They often struggle to find a suitable word that expresses the meaning in their minds. This problem must be addressed as quickly as possible so as not to discourage the learner from practicing speaking. To that end, this study was conducted using a qualitative approach, including desk and field research. Data for this study was collected by observing the reality at Mafaza Institute in Indonesia during the education process, as well as through documenting relevant books and articles. After conducting this study, researchers concluded that the use of crosswords could provide learners with the ability and skill to speak, thus overcoming the major obstacle of difficulty in retrieving vocabulary while speaking. Additionally, crosswords can help prevent boredom among learners and boost their enthusiasm for learning. It is recommended in this study that every teacher craft crosswords based on the vocabulary taught in the classroom rather than just copying and pasting ready-made crosswords from the internet, which often do not align with students' needs. The purpose is to train and practice learners in retrieving vocabulary, making it easier for them to express themselves when speaking, and allowing them to engage in dialogue with friends or teachers more effectively.